2019
DOI: 10.3389/frobt.2018.00139
|View full text |Cite
|
Sign up to set email alerts
|

Intentional Mindset Toward Robots—Open Questions and Methodological Challenges

Abstract: Natural and effective interaction with humanoid robots should involve social cognitive mechanisms of the human brain that normally facilitate social interaction between humans. Recent research has indicated that the presence and efficiency of these mechanisms in human-robot interaction (HRI) might be contingent on the adoption of a set of attitudes, mindsets, and beliefs concerning the robot's inner machinery. Current research is investigating the factors that influence these mindsets, and how they affect HRI.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…Together the correlation patterns suggest that the more negative someone is regarding robots, the less s/he is influenced by the presence of the robot and the less s/he shows social facilitation effect. Such a result is in line with the hypothesis of Schellen and Wykowska [11], that negative attitudes towards robots might be a moderating factor for social presence effects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Together the correlation patterns suggest that the more negative someone is regarding robots, the less s/he is influenced by the presence of the robot and the less s/he shows social facilitation effect. Such a result is in line with the hypothesis of Schellen and Wykowska [11], that negative attitudes towards robots might be a moderating factor for social presence effects.…”
Section: Discussionsupporting
confidence: 90%
“…Another crucial aspect to examine in HRI is how individual differences in robot perception translate to differences in behavior [11,12]. Indeed, individual differences, such as personality traits or attitudes, have been found to affect the perception and acceptance of robots in social situations [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…, 2017 ; Chevalier et al. , 2019 ; Schellen and Wykowska, 2019 ). Regarding ecological validity, it has been shown that robots that are embodied increase social presence ( Jung and Lee, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adopting the intentional stance toward robots can also have positive effects on human performance in HRI as they can facilitate learning (Brown and Howard, 2013 ), improve physical interactions where hand–eye coordination is needed (Carter et al, 2014 ), induce social facilitation effects (Bartneck, 2003 ; Woods et al, 2005 ; Looije et al, 2010 ), and improve interactions in team settings (Breazeal et al, 2005 ). By the same token, not adopting the intentional stance toward social robots can pose a problem for HRI, as humans might be engaging fewer socio-cognitive mechanisms in social interactions with robots, and thereby less social attunement (i.e., activation of socio-cognitive mechanisms) occurs between the two agents (Wiese et al, 2012 , 2018 ; Wykowska et al, 2014 ; Özdem et al, 2016 ; Caruana et al, 2017 ; Ciardo et al, 2020 ; for a review, see Perez-Osorio et al, 2015 ; Wiese et al, 2017 ; Schellen and Wykowska, 2019 ).…”
Section: Introductionmentioning
confidence: 99%